Factors Affecting Intention to use the Gamification Feature in Ruang Guru - Jacques; Gunawang Wang (Universitas Pendidikan Ganesha, 2025)
The The rapid development of educational technology has encouraged the integration of gamification into online learning to enhance students’ motivation and engagement. However, its utilization has not been supported by a comprehensive understanding of the factors influencing users’ intention to adopt it, particularly regarding user experience complaints. This study aims to analyze the key factors influencing students’ intention to use the AdaptoX gamification feature on the online learning platform Ruangguru.This study employed a quantitative approach with a survey design, adopting the Technology Acceptance Model (TAM) framework extended with perceived enjoyment, social influence, and hedonic motivation variables. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4 software. The results indicate that perceived ease of use, perceived usefulness, perceived enjoyment, hedonic motivation, and attitude significantly influence the intention to use gamification features, while social influence does not show a significant effect. The findings reveal that usage intention is more influenced by personal experience and intrinsic value than by social pressure. The success of gamification adoption depends on usability, ease of use, and enjoyable learning experiences. This study emphasizes the importance of developing gamification features that focus on user experience, intrinsic motivation, and ease of use to enhance online learning adoption.